Mitigating CO2 Emissions: The Synergy of Foreign Direct Investment and Renewable Energy in Europe and Central Asia - Dagmar Skodova Parmová; Tulkin Teshabaev; Nargiza Kasimova; Raufhon Salahodjaev (International Journal of Energy Economics and Policy, 2024)
This study investigates the impact of renewable energy and Foreign Direct Investment (FDI) on CO2 emissions across 45 countries in Europe and Central Asia for the period of 2000-2019. Utilizing the two-step system Generalized Method of Moments (GMM) estimator, our findings reveal that both FDI and renewable energy play pivotal roles in mitigating CO2 emissions. Notably, countries with higher levels of renewable energy integration experience a stronger reduction in CO2 emissions due to FDI. Furthermore, our analysis uncovers an inverted U-shaped relationship between GDP per capita and CO2 emissions, indicating a nuanced trajectory of environmental impact with economic growth. Additionally, our study identifies an inverse correlation between CO2 emissions and the agriculture sector as well as government size. The implications of these findings are discussed in the context of policy strategies, providing valuable insights for sustainable development in the Europe and Central Asia region.